Redefinition of the sexstrigatus group of Lasioglossum (Hemihalictus) Cockerell, 1897 (Hymenoptera, Apoidea, Halictidae), with a revision of Japanese species - Murao, Ryuki (European Journal of Taxonomy, 2021)
I propose a redefinition of the sexstrigatus group of Lasioglossum (Hemihalictus) Cockerell, 1897, including a phylogenetic analysis. This group is characterised by a combination of the following 12 characteristics: male antenna short, not attaining to metasoma, male labrum with distal process and well-developed basal elevation, male head with genal process as variation, female mesepisternum reticulate-punctate on lower area, mesepisternum without tubercle in both sexes, female metasomal terga with distinct fimbriae on posterior margin, male S8 with well-developed median process, gonobase ventral arm of male genitalia connected with each other at upper ends, gonocoxite of male genitalia smooth, gonostylus of male genitalia small and simple, bud-like, and the ventral retrorse lobe of male genitalia not attaining to gonobase. The Japanese species of the sexstrigatus group are revised. Thirteen species in total are recognised, including three new species: Lasioglossum (Hemihalictus) ikudomei sp. nov., L. (H.) spectrum sp. nov., and L. (H.) subsimplicior sp. nov. Lasioglossum (Hemihalictus) perplexans (Cockerell, 1925) is synonymised under L. (H.) kiautschouense (Strand, 1910). A key to the Japanese species is provided. Bionomical data, such as flight and flower records or habitat, are reported for some species. The distributions of all species are mapped. DNA sequences including a part of the barcode region are given for L. (H.) kiautschouense, L. (H.) ohei Hirashima & Sakagami, 1966, L. (H.) speculinum (Cockerell, 1925), L. (H. ) spectrum sp. nov., L. (H. ) subsimplicior sp. nov., and L. (H. ) taeniolellum (Vachal, 1903).